Usage of human diatomaceous earth - Joseph Mwangi (Annals of Limnology and Oceanography - Peertechz Publications, 2023)
Diatomaceous earth is naturally formed sedimentary mineral rock resulting from the remains of diatoms, or oceanic unicellular algae. It is extracted from diatoms mined from deposits of diatomite and manufactured into a powder that is diatomaceous earth for human use, as a natural compound. It is gaining popularity as having an outstanding list of health benefits and non-toxic, no-known side effect origins. In this paper, a comprehensive review is presented to highlight the availability, benefits, mechanism of operation, and effects on the use of Human Diatomaceous Earth. The review revealed that diatomaceous earth has an outstanding list of health benefits and non-toxic, no-known side effects. It has the ability to lower the concentration of cholesterol in the blood. It is a very essential mineral for tendons, cartilage, blood vessels, and bones. Diatomaceous Earth is also considered to greatly help the body in getting rid of toxic substances such as heavy metals. It improves body joints bones, and ligaments through silica, which is the highest-occurring compound in diatomaceous earth that aids in the metabolism and formation of the joints.